Technological Evolution in Information Security: A Cryptographic Perspective - Sriramudu, Sriramudu; Padmavathi, G; Yerukala, Nagendar; Guntupalli, Neelima (International Journal of Computer Sciences and Engineering, 2024)
This paper gives a critical review of the evolution of encryption methodologies with regard to their function within the technological field in ensuring cryptographic security. It starts with an overview of traditional methods of encryption, including character replacement methods, then classical encryption methods. It progresses through the electrical and electronic machine-based method of developing newer techniques up to the modern ones, such as digital machines, quantum machines, and post-quantum ciphers. This is followed by simulations, software-based generation of cipher text, thus forming an overview of the cryptographic technologies in use. Examples of formats for ciphers are provided to show how, in practice these encryption methods apply to real-world-type situations or scenarios. Maybe, through such observation, the paper is trying to enlighten its audience with regard to the dynamic nature of cryptographic security and its place in modern technology.